Infusing Islamic-related content through Trivia Cards: Research & development in ESP classroom - Rafika Rabba Farah (EduLite: Journal of English Education, Literature and Culture, 2020)
English learning has now largely been driven by global socioeconomics. Thus, English for Specific Purposes is likely taught at tertiary level education in Asia. Especially, in Indonesia, where Muslim is the major population, teaching English to students majoring in Islamic Studies must be carefully planned. Experts have discussed widely that English language has its association to Western civilization and Christian value. Therefore, this present research aims at developing Trivia Cards which infuse Islamic elements to teach English for Islamic Studies for students majoring in Islamic discipline at one private Islamic university in Indonesia. Research and Development (R&D) was implemented in the study involving some procedures as follows: need analysis, product design, product validation, and revision. Results on need analysis comprised five important topics, they were Islamic manner (akhlak), oneness of God (tauhid), Islamic history, and hadith. Further, the experts highlighted that the media developed reached its validity criteria as it was scored 98.07% by media-language expert; and scored 88.6% by content expert. Furthermore, the study were 95% positively responded by the respondents with 45% strongly agreed and 50% agreed respectively; meanwhile only small portion stated his/her disagreement for 5% or as many of one respondent. Thus, this study has shed a light that Islamic content can provide a way for English teachers to teach English to students with Muslim background.